The Gospel According To Jesus What Is Authentic Faith? - MacArthur, John (Grand Rapids Zondervan, 2009)
What does Jesus mean when he says, "Follow me"? Twenty years ago, pastor-teacher and bestselling author John MacArthur tackled that seemingly simple question-- and wrote a book that has since taken its place among Christianity's classics.
Keywords: Jesus Christ -- Person and offices. Christian life. Jesus Christ